Clinical implications of cytogenetic heterogeneity in Philadelphia chromosome positive (Ph+) adult B cell acute lymphoblastic leukemia following tyrosine kinase inhibitors and chemotherapy regimens. (September 2019) - Jain, Poonam; Gu, Jun; Kanagal-Shamanna, Rashmi; Tang, Zhenya; Patel, Keyur P.; Yao, Hui; Fang, Lianghua; Bao, Hai-Yan; Liu, Ching-Hua; Lin, Pei; Medeiros, L.Jeffrey; Lu, Xinyan
Highlights: Ph+B-ALL are cytogenetically heterogeneous and ACAs are frequent. Variant-/complex-t(9;22) and clone numbers are independent high-risk factors. Chromosome analysis is valuable for assessing clonal heterogeneity in Ph+B-ALL. Abstract: We retrospectively studied a cohort of 144 adults with Philadelphia chromosome/ BCR -ABL 1 positive B acute lymphoblastic leukemia (Ph + B-ALL) to assess the clinical implications of cytogenetic heterogeneity in this disease. The study group included 85 men and 59 women that were sorted into 6 subgroups based on karyotypic findings in the stemline as follows: 32 patients with t(9;22) as a sole aberration, 23 with t(9;22) plus 1 additional chromosomal abnormality (ACA), 26 with t(9;22) as part of a complex karyotype, 18 showing a variant-/complex- t(9;22), 30 with t(9;22) as the stemline with ACAs in the sideline(s), and 15 patients who had the t(9;22) and hyperdiploidy. In 89 patients 1 clone was identified; 41 had 2 clones and 14 had ≥ 3 clone(s). The median overall survival (OS) was 25.6 months and the median relapse-free survival (RFS) was 20.6 months. Patients with variant-/complex- t(9;22) had poorer OS and RFS when compared with all other subgroups combined ( P = 0.0018 and P = 0.0049, respectively). In addition, patients with ≥ 2 clones had worse OS and RFS than patients with 1 clone ( P = 0.0179 and P = 0.0429, respectively). Multivariate analysis confirmed that variant-/complex-t(9;22) and clone number are independent risk factors. We suggest that conventional chromosomal analysis is of clinical importance for risk stratification of B-ALL patients.